P863 Large pericardial effusion two months after transcatheter aortic valve implantation: case report of a post-cardiac injury syndrome. (17th January 2020) - Alves Pinto, R; Martins Carvalho, M; Proenca, T; Araujo, P M; Nunes, A; Torres, S; Grilo, P D; Resende, C X; Dias, P; Almeida, R; Silva, J C; Maciel, M J; et al.
Abstract: We present a case of a 87-year-old female with a symptomatic severe aortic stenosis (aortic valve area 0.9 cm2, mean transvalvular pressure gradient 44 mmHg). She was refused to surgical aortic valve replacement due to marked aortic root calcification. A transcatheter aortic valve (ACCURATE neo™ 27) was electively implanted. In immediate post-procedure, the patient presented an episode of hypotension, rapidly reverted with supportive treatment. A transthoracic echocardiogram (TTE) showed a circumferential mild pericardial effusion (PE) without prosthetic valve disfunction and with preserved biventricular systolic function. Due to paroxysmal episodes of atrial fibrillation, it was decided to withdraw anti-aggregation and to start anticoagulation. Four days after transcatheter aortic valve implantation (TAVI) the patient presented newer intraventricular and atrioventricular conduction disturbance (left bundle branch block and type-I second-degree atrioventricular block). A definitive pacemaker was implanted without complications. PE maintained stable and seven days after TAVI the patient was discharged from hospital. Two months after TAVI, the patient was admitted to Intensive care unit (ICU) with increasing asthenia, dyspnea and pleuritic thoracic pain over the preceding two weeks. Laboratory workup exhibited elevation of inflammatory markers (leukocytosis and C-reactive protein). A TTE was performed and showed a large circumferential PE (29 mm) with signs of hemodynamic impact (swinging heart, inferior vena cava dilation with <50% inspiratory collapse, right atrial collapse >1/3 of cardiac cycle, proto-diastolic right ventricular collapse and mitral respiratory flow variation >25%). The patient started treatment with anti-inflammatory drugs (aspirin 1000mg every 8h plus colchicine 0.5mg twice daily) and pericardiocentesis was initially postponed. In spite of clinical and echocardiographic improvement, she maintained elevated inflammatory markers and a moderate PE. Prednisolone 30mg daily was added to initial therapy and serial evaluations showed a pronounced reduction of PE as well as of inflammatory markers. Two weeks after admission to ICU the patient was discharged with a residual PE measuring less than 5mm. The previous recent cardiac intervention and the effective response to anti-inflammatory treatment suggest a post-cardiac injury syndrome. This case report wants to show that post-cardiac injury syndrome is a diagnosis that should be keep in mind after TAVI.